qPCR estimates of Babesia bovis and Babesia bigemina infection levels in beef cattle and Rhipicephalus microplus larvae - Giglioti, Rodrigo [UNESP]; Oliveira, Henrique Nunes de [UNESP]; Okino, Cintia Hiromi; Sena Oliveira, Marcia Cristina de (Springer, 2018)
Babesia spp. are tick-transmitted intraerythrocytic apicomplexan parasites that infect wild and domestic animals. Babesia bovis and B. bigemina are endemic and responsible for enormous economic losses to the livestock industry in most of the Brazilian territory, wherein the tick Rhipicephalus microplus is the unique vector. Better understanding of epidemiology and parasite-host interactions may improve the tools for disease control and genetic management for selection of resistant animals. This study aimed to detect, quantify and measure the correlation between B. bigemina and B. bovis infection levels in bovine blood and into tick, by absolute quantification of hemoparasite DNA using qPCR. Blood bovine samples and larvae pools from 10 engorged R. microplus females were collected from each Canchim heifers (5/8 Charolais + 3/8 zebu, n = 36). All evaluated samples were positive for both Babesia species tested. Correlations of B. bovis and B. bigemina levels between cattle and tick host were 0.58 and 0.66, respectively. These high positive correlation coefficients indicate that parasitemia load in the bovine may be dependent on or may determine the parasitemia load in the ticks.
Keywords: Correlation; Infection; Babesiosis; Cattle; Ticks